Prevalence And Risk Factor Assessment Of Bovine Eimeriosis In Internal Drainage Dry Zone Of Rajasthan (India) (Applied Biological Research, 2018)
The examination of 609 faecal samples, randomly collected from Internal  drainage dry zone of Rajasthan from September 2016 to August 2017 for prevalence of various species of Eimeria affecting the health of dairy  animals, revealed an overall prevalence of 32.68%. Risk assessment analysis  revealed highest prevalence in native cattle (33.04%), followed by crossbred  cattle (32.75%) and buffaloes (32.46%) in decreasing order of prevalence  having non-significant difference. Severity analysis based on the estimation  of oocysts per gram (OPG) of faeces revealed mild to moderate infection of Eimeria spp. ranging from 300-2500 with an average of 1450±334.42 OPG  in dairy animals of study area. Microscopic examination of sporulated  oocysts revealed the presence of six morphotypes of Eimeria viz., E. bovis (38.2%) as the major contributor to coccidia population, followed by E.  zuernii (16.4%), E. cylindrica (15.4%), E. auburnensis (13.4%), E. pellita  (11.4%) and E. alabamensis (5.2%) in a decreasing order of prevalence.
Keywords: Coccidiosis; dairy animals; internal drainage dry zone; morphotypes; risk assessment; strategic control